Functional Oxides Nanomaterials for the Removal of Dyes - Umaru, Isaac John; Agwu, James Eneji (Darul Yasin Al Sys, 2025)
The elimination of dyes from wastewater represents a critical environmental challenge, as dye effluents from industries such as textiles, printing, and paper production pose significant risks to ecosystems and human health. Conventional treatment methods are often limited in efficiency and cost-effectiveness, necessitating the exploration of advanced alternatives. This review analyzes the application of functional oxide nanoparticles in dye removal, with particular focus on metal oxides such as titanium dioxide, iron oxide, and zinc oxide, as well as mixed metal oxides. These nanomaterials exhibit exceptional adsorption and photocatalytic properties due to their large surface area, tunable surface chemistry, and distinctive surface characteristics, which enhance dye removal efficiency. The adsorption mechanisms involve electrostatic attraction, hydrogen bonding, and π–π stacking interactions, while photocatalytic degradation relies on the generation of reactive oxygen species under light irradiation, allowing complete dye mineralization and minimizing harmful intermediates. Despite these advantages, further research is needed to evaluate long-term stability, recyclability, and potential ecological impacts, alongside the development of cost-effective synthesis methods and innovative nanomaterials with improved performance.